An analysis of the socioeconomic and political status of Muslims in India - Alam, Mohammad Shekaib Alam; Abdelsalam, El Fatih Abdullahi (International Journal for Multidisciplinary Research, 2023)
This study investigates the socioeconomic and political standing of the Muslim population in India. The scope of this inquiry has been restricted to particularly examine three areas: education, employment, and political representation. The presence of a different array of criteria can be ascribed to the analysis of the presented scenario for each of the groups. Darin-Mattsson, Fors, and Kåreholt (2017) have noted that several strategies have been employed to operationalize the idea of socioeconomic status. Among these ways, education, social class, and income have emerged as the primary indicators. Therefore, this paper examines the circumstances of Muslims based on the specified criteria mentioned in line three. It concludes that Muslims are encountering significant challenges in all of these areas, and the government appears to be disinterested in their plight. Instead, it appears that their marginalisation and confinement to specific areas is rising, and they are viewed as troublesome and suspicious in society.